Analysis of Regional Financial Capacity in Sumatera-Indonesia - Dafina Nur Intan; Azansyah Azansyah (East Asian Journal of Multidisciplinary Research, 2023)
The objectives of this research are: (1) To analyze the financial capability of the Regency/city in the region of southern Sumatra and (2) the compare of financial capability of the district/parent city with the expansion in the region of Sumatra. This research is a quantitative study with a sample of district/parent city and expansion in the region of Sumbagsel. The data analysis methods used are analysis of financial ratios and descriptive analysis. The results show The District/parent city and District/city expansion has a ratio of self-reliance, degree of fiscal decentralization and a fluency index of routine capabilities, were.